4(2x+3y-4z)=

Simple and best practice solution for 4(2x+3y-4z)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x+3y-4z)= equation:


Simplifying
4(2x + 3y + -4z) = 0
(2x * 4 + 3y * 4 + -4z * 4) = 0
(8x + 12y + -16z) = 0

Solving
8x + 12y + -16z = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12y' to each side of the equation.
8x + 12y + -12y + -16z = 0 + -12y

Combine like terms: 12y + -12y = 0
8x + 0 + -16z = 0 + -12y
8x + -16z = 0 + -12y
Remove the zero:
8x + -16z = -12y

Add '16z' to each side of the equation.
8x + -16z + 16z = -12y + 16z

Combine like terms: -16z + 16z = 0
8x + 0 = -12y + 16z
8x = -12y + 16z

Divide each side by '8'.
x = -1.5y + 2z

Simplifying
x = -1.5y + 2z

See similar equations:

| 5(m-3)=20 | | 3(a+2)=9 | | 5(3r-1)=40 | | -8x-2(x-3)=6 | | 4(y+8)=12 | | 25x^2-20x-75=0 | | 2(p-3)=14 | | -3y=8-5 | | -3y=8-2 | | n+d=90 | | -3y=10-10 | | 2(x+5)=2(x-6) | | (3+5x)(2-3x)=12-(5x)2 | | -3y=10-4 | | 0=16X^2+90X+12000 | | (4-3j)+(-6+8j)+(7+10j)-(1-5j)= | | 25y+8=15y-2 | | 19x*17x=696705.438 | | 3x+13=2x+6 | | -2y=0+2 | | -2y=0-1 | | -2y=0-0 | | 36x-2=48x-5 | | 8e+1=31 | | 17x+8y=388 | | 2y=-4-2 | | 2y=-4-4 | | -2y=12-6 | | (5+2j)+(7+j)= | | -2y=12-12 | | ln(5x-3)+ln(x+2)=ln(5x^2+9) | | 3y=9-1 |

Equations solver categories